Two Independent Value Orientations: Ideal and Counter-Ideal Leader Values and Their Impact on Followers’ Respect for and Identification with Their Leaders - Graf, Matthias M.; Quaquebeke, Niels van 1977-; Dick, Rolf van 1967- (2011)
Traditionally, conceptualizations of human values are based on the assumption that individuals possess a single integrated value system comprising those values that people are attracted by and strive for. Recently, however, van Quaquebeke et al. (in J Bus Ethics 93:293–305, 2010) proposed that a value system might consist of two largely independent value orientations—an orientation of ideal values and an orientation of counter-ideal values (values that individuals are repelled by), and that both orientations exhibit antithetic effects on people’s responses to the social world. Following a call for further research on this distinction, we conducted two studies to assess the independent effects of ideal and counter-ideal values in leadership settings. Study 1 (N = 131) finds both value orientations to explain unique variance in followers’ vertical respect for their leaders. Study 2 (N = 136) confirms these results and additionally shows an analogous effect for followers’ identification with their leaders. Most importantly, we find that both value orientations exhibit their effects only independently when the content of the two orientations pertain to different value types in Schwartz’s (in J Soc Issues 50:19–46, 1994) circumplex model. Implications for theory and practice are discussed.
Keywords: Identification with leaders; Respect for leaders; Leadership; Counter-ideal values; Ideal values